Reimagining Islamic Education: A Transformative Approach through Spirituality, Digital Literacy, and Bugis Indigenous Values - Elihami, Elihami (Sublim: Jurnal Pendidikan, 2025)
This study explores a transformative framework for Islamic education that synergizes spirituality, digital literacy, and Bugis indigenous values. In an era marked by rapid technological advancements and spiritual disorientation, Islamic education must move beyond traditional pedagogies to embrace contextual, integrative approaches. Drawing upon Seyyed Hossein Nasr’s metaphysical perspective on spirituality and the local wisdom embodied in the Bugis concept of Pappijeppu—which emphasizes harmony, compassion, and moral responsibility—this paper proposes a model that nurtures holistic human development. Using qualitative methods, including ethnographic observation, textual analysis, and expert interviews in South Sulawesi, Indonesia, the research reveals that incorporating digital literacy with spiritual and cultural values enhances students’ critical thinking, ethical awareness, and identity formation. The findings underscore the urgent need to reimagine Islamic education as a transformative process that is deeply rooted in tradition while responsive to the challenges of the digital age